(untitled) (Philology, 2026)
This article examines whether in the absence of lexically specified stress a default phonological stress emerges in Bulgarian language. The study on acronym accentuation, based on dictionary data reveal domination of penultimate accent among V-final units and ultimate accent among C-final ones. The results represent a harmonic grouping and also could be interpreted as accent orientation towards the right boundary of the word stem. The lexical frequency effect also play a role.